Lifetime Measurements at NCSR “Demokritos” - Ashley, S. F.; Axiotis, M.; Foteinou, V.; Harrisopulos, S.; Konstantinopoulos, T.; Lagoyannis, A.; Mertzimekis, T. J.; Provatas, G. (HNPS Advances in Nuclear Physics, 2020)
Proof-of-principle inelastic proton scattering measurements have been performed at NCSR “Demokritos”. Excited states in 64Zn and 92Mo were populated using the (p,p'γ) reaction with E(p) = 7 MeV. The reaction γ rays were detected using four HPGe detectors at eight separate angles, with respect to the beam-axis. From Doppler-shift attenuation of the ∞ rays, lifetimes for eight excited states in 64Zn and for the Iπ = 2^+_2 and 2^+_3 states in 92Mo were deduced. The lifetimes measured in 92Mo are in good agreement with adopted values whereas the lifetimes measured in 64Zn are typically longer than the literature values. Development of the experimental set-up and potential novel physics cases where this reaction could be used are briefly discussed.